An analysis of the consequences of acute appendicitis between urban and rural patients in Bangladesh - Tasnuva Iqbal, Khondker Abul Kalam Azad, Muhammad Irfanul Alam, Mainul Haque (Journal of Applied Pharmaceutical Science, 2021)
In acute appendicitis, timely diagnosis and rapid intervention are critical for effective management. However, geographic location and socioeconomic context can play an important role in developing countries’ clinical course and outcome. The aim of this study is to observe the consequences of acute appendicitis between urban and rural patients. A prospective analytical study was conducted from April 25 to October 25, 2016, in Chittagong Medical College Hospital, Chattogram, Bangladesh. A total of 200 patients, 100 patients in each arm with a clinical diagnosis of acute appendicitis, were enrolled. 33.5% were in the age group of 21–30 years. The male:female ratio was 1.94:1. 45% of the urban patients came from the middle class, while 47% of the rural patients were from poor socioeconomic backgrounds. The mean duration of the presentation was 2.96 ± 1.88 days in urban and 5.28 ± 2.8 days in rural patients. 87% of urban and 33% of rural patients received conservative treatment before hospitalization. 74.11% of rural and 30% of urban patients delayed consenting to surgery. Perforation was found in 17.78% of urban and 33.33% of rural patients and gangrenous appendicitis in 12.22% of urban and 66.67% of rural patients. Rural patients suffered more complications like wound infection (34.4% and 68.4%, resp.), septic shock (0% and 7.9%, resp.), burst abdomen (0% and 5.3%, resp.), and death in two rural patients. Mean hospital stay was 4.37 ± 1.69 days in urban and 8.41 ± 2.44 days in rural patients. The rural population has higher morbidity and mortality when compared to the urban population of Bangladesh.
Keywords: Acute disease, appendicitis, epidemiology, appendicitis, surgery, humans, male, female, morbidity/trends, prospective studies, rural population, Bangladesh, urban population.